Summing Across Different Active Zones can Explain the Quasi-Linear Ca2+-Dependencies of Exocytosis by Receptor Cells - Heil, Peter; Neubauer, Heinrich (Frontiers in Synaptic Neuroscience, 2010)
Several recent studies of mature auditory and vestibular hair cells, and of visual and olfactory receptor cells, have observed nearly linear dependencies of the rate of neurotransmitter release events, or related measures, on the magnitude of Ca2+-entry into the cell. These relationships contrast with the highly supra-linear, 3rd to 4th power, Ca2+-dependencies observed in most preparations, from neuromuscular junctions to central synapses, and also in hair cells from immature and various mutant animals. They also contrast with the intrinsic, biochemical, Ca2+-cooperativity of the ubiquitous Ca2+-sensors involved in fast exocytosis (synaptotagmins I and II). Here, we propose that the quasi-linear dependencies result from measuring the sum of several supra-linear, but saturating, dependencies with different sensitivities at individual active zones of the same cell. We show that published experimental data can be accurately accounted for by this summation model, without the need to assume altered Ca2+-cooperativity or nanodomain control of release. We provide support for the proposal that the best power is 3, and we discuss the large body of evidence for our summation model. Overall, our idea provides a parsimonious and attractive reconciliation of the seemingly discrepant experimental findings in different preparations.